Viscosity of heavy n-alkanes and diffusion of gases therein based on molecular dynamics simulations and empirical correlations - Makrodimitri, Zoi A.; Heller, Andreas; Koller, Thomas Manfred; Rausch, Michael Heinrich; Fleys, Matthieu S. H.; Bos, A. N. Rene; van der Laan, Gerard P.; Fröba, Andreas Paul; Economou, Ioannis G. (Journal of Chemical Thermodynamics, 2015)
The viscosity of pure n-alkanes and n-alkane mixtures was studied by molecular dynamics (MD) simulations using the Green-Kubo method. n-Alkane molecules were modeled based on the Transferable Potential for Phase Equilibria (TraPPE) united atom force field. MD simulations at constant number of molecules or particles, volume and temperature (NVT) were performed for n-C-8 up to n-C-96 at different temperatures as well as for binary and six-component n-alkane mixtures which are considered as prototypes for the hydrocarbon wax produced during the Gas-To-Liquid (GTL) Fischer-Tropsch process. For the pure n-alkanes, good agreement between our simulated viscosities and existing experimental data was observed. In the case of the n-alkane mixtures, the composition dependence of viscosity was examined. The simulated viscosity results were compared with literature empirical correlations. Moreover, a new macroscopic empirical correlation for the calculation of self-diffusion coefficients of hydrogen, carbon monoxide, and water in n-alkanes and mixtures of n-alkanes was developed by combining viscosity and self-diffusion coefficient values in n-alkanes. The correlation was compared with the simulation data and an average absolute deviation (AAD) of 11.3% for pure n-alkanes and 14.3% for n-alkane mixtures was obtained. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Molecular dynamics simulation; Viscosity; Diffusion coefficient; Heavy n-alkanes